Bovine Ephemeral Fever Virus - Bulut, Hakan; Azkur, Ahmet Kursat (CRC Press, 2015)
Bovine ephemeral fever (BEF; also known as 3-day sickness) is a vector-borne, viral disease of cattle and water buffaloes that leads to dramatic loss in milk production. The disease in cattle is characterized by acute febrile reaction, stiffness, lameness, and spontaneous recovery within 3 days [1]. The mortality rate was reported as 1%-3% in the past outbreaks, but about 20% was noted in some herd of the recent outbreaks [2]. The most important vector of the causal agent bovine ephemeral fever virus (BEFV) is Culicoides flies. Although the disease has been reported in the tropical and subtropical regions of Australia, Africa, and Asia, considering that Culicoides flies are transported to long distances especially by wind, BEFV may spread to wider geographies or continents in recent years [1-3]. Given the increased number of epidemics and high mortality rates observed in recent outbreaks of BEF, with devastating economic consequences, it is critical that rapid, sensitive, and specific diagnostic methods are available and applied for improved detection and monitoring of BEFV. © 2016 by Taylor & Francis Group, LLC.